Antifascist dad : urgent conversations with young people in chaotic times - Remski, Matthew D., 1971- (North Atlantic Books, 2026)
"A guide for parents on fighting the rise of far-right extremism with their children; conversations on resisting despair, building resilience, and divesting from toxic masculinity"-- Provided by publisher.